Value of ultrasound-guided wire localization resection for non-palpable breast lesions - ZHANG Lu, LI Zhi, SUI Hao, SHI Li-hui (Jichu yixue yu linchuang, 2020)
Objective To evaluate the clinical value of ultrasound-guided wire localization resection for non-palpable breast lesions. Methods One hundred and thirty-three cases of breast lesions which were detected by ultrasonography but negative palpation were selected. Under the guidance of ultrasound, the localized guide wire was placed into the breast lesion, and the whole lesion and part of the surrounding normal tissue were removed according to the position of the localized guide wire, and the lesions were sent for pathological examination. Results Total of 136 nodules were found in 133 patients, including 9 cases of intraductal papilloma, 25 cases of mammary hyperplasia with fibroadenomatous structure formation, 4 cases of atypical hyperplasia, 35 cases of mammary hyperplasia, 53 cases of fibroadenoma, 8 cases of invasive breast cancer and 2 cases of ductal carcinoma in situ. Conclusions Ultrasound-guided wire localization resection for the treatment of non-palpable breast lesions has the advantages of accurate positioning, simple operation and non-invasive, etc. The application of this technique is of great value for the early diagnosis and treatment of breast cancer.